Answer:
9/49
Step-by-step explanation:
4 purple beads and 3 green beads= 7 beads
P( green) = green = total = 3/7
Replace the bead
4 purple beads and 3 green beads= 7 beads
P( green) = green = total = 3/7
P( green , replace, green) = 3/7 * 3/7 = 9/49
Answer: Y=-1 or Y=-1+4
Step-by-step explanation:
<h3>Use the formula y2- y1 over x2-x1 so it should look like this 1-3 over 3-1 which is -2 over 2 then you divide that which is -1 and if you have to find one all you have to do is use one point label which is x and y so I pick (1,3) so you put 3=-1(1) once you have that you multipy so -1 times 1 is -1 so your gonna add 1 to the -1 and the three the -1 cancel out because it is a zero pair 3+1 is 4 so B=4 </h3>
Answer:
see below
Step-by-step explanation:
t = 7m
Let m = 6
t = 7*6 = 42
Let m = 8
t = 7*8
t = 56
9514 1404 393
Answer:
√3
Step-by-step explanation:
The ratio of the short sides to the hypotenuse in an isosceles right triangle is ...
1 : 1 : √2
This means ...
p·√2 = √6
p = (√6)/(√2) = √(6/2)
p = √3
Answer:
attached
Step-by-step explanation:
y=|4-3x| y: positive number